Energy Efficient Homes: The Duct System - Wendell A. Porter; Hyun-Jeong Lee; Kathleen C. Ruppert; Randall A. Cantrell (EDIS)
The duct, or air distribution, system used in cooling and heating your home is a collection of tubes that distributes the heated or cooled air to the different rooms. Typical duct systems lose 25 to 40% of the heating or cooling energy put out by the cooling and heating system. Learn about common problems and ways to get the most out of your duct system. This revised 4-page fact sheet was written by Wendell A. Porter, Hyun-Jeong Lee, Kathleen C. Ruppert, and Randall A. Cantrell, and published by the UF Department of Family Youth and Community Sciences, August 2011.